Selection for nonspecific adhesion is a driver of FimH evolution increasing Escherichia coli biofilm capacity. Issue 1 (5th April 2022) - Yoshida, Mari; Thiriet-Rupert, Stanislas; Mayer, Leonie; Beloin, Christophe; Ghigo, Jean-Marc
ABSTRACT: Bacterial interactions with surfaces rely on the coordinated expression of a vast repertoire of surface-exposed adhesins. However, how bacteria dynamically modulate their adhesion potential to achieve successful surface colonization is not yet well understood. Here, we investigated changes in adhesion capacity of an initially poorly adherent Escherichia coli strain using experimental evolution and positive selection for mutations improving adhesion and biofilm formation on abiotic surfaces. We showed that all identified evolved populations and clones acquired mutations located almost exclusively in the lectin domain of fimH, the gene coding for the α-d -mannose-specific tip adhesin of type 1 fimbriae, a key E. coli virulence factor. While most of these fimH mutants showed reduced mannose-binding ability, they all displayed enhanced binding to abiotic surfaces, indicating a trade-off between FimH-mediated specific and nonspecific adhesion properties. Several of the identified mutations were already reported in the FimH lectin domain of pathogenic and environmental E. coli, suggesting that, beyond pathoadaptation, FimH microevolution favoring nonspecific surface adhesion could constitute a selective advantage for natural E. coli isolates. Consistently, although E. coli deleted for the fim operon still evolves an increased adhesion capacity, mutants selected in the ∆ fim background are outcompeted by fimH mutants revealing clonal interference for adhesion. Our study therefore provides insights into the plasticity of E. coli adhesion potential and shows that evolution of type 1 fimbriae is a major driver of the adaptation of natural E. coli to colonization. Abstract : Experimental evolution showed that mutations in type 1 fimbriae FimH lectin are the main drivers of the acquisition of nonspecific surface adhesion and biofilm capacity in natural Escherichia coli isolates.